2015
DOI: 10.1007/s10067-015-2898-x
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in rheumatoid arthritis

Abstract: The role of genetic and epigenetic factors in the development of rheumatic diseases has been an interesting field of research over the past decades all around the world. Research on the role of microRNAs (miRNAs) in rheumatoid arthritis (RA) has been active and ongoing, and investigations have attempted to use miRNAs as biomarkers in disease diagnosis, prognosis, and treatment. This review focuses on experimental researches in the field of miRNAs and RA to present the data available up to this date and include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 103 publications
0
48
0
Order By: Relevance
“…As such, dysregulation of miRNA seen in disease models, including psoriasis, multiple sclerosis, and rheumatoid arthritis, has become a topic of major interest for possible therapeutic targets [37]. In the current study, we identified two miRNA and two target genes as possible therapeutic modalities: miR-21 with its target SMAD7 and miR-29b with its target IFN-γ.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…As such, dysregulation of miRNA seen in disease models, including psoriasis, multiple sclerosis, and rheumatoid arthritis, has become a topic of major interest for possible therapeutic targets [37]. In the current study, we identified two miRNA and two target genes as possible therapeutic modalities: miR-21 with its target SMAD7 and miR-29b with its target IFN-γ.…”
Section: Discussionmentioning
confidence: 86%
“…As such, dysregulation of miRNA seen in disease models especially those considered inflammatory and/or autoimmune has become a topic of major interest for possible therapeutic targets [37]. The importance of miRNA in hypersensitivity was recently highlighted by the observance of similarly elevated miRNA expression in both human and mouse allergic contact dermatitis skin samples [38].…”
Section: Resultsmentioning
confidence: 99%
“…In RA, miRNAs act as proinflammatory or anti‐inflammatory regulators at the post‐transcriptional level . Up until now, the role of miRNA during melatonin administration in RA has not been described.…”
Section: Resultsmentioning
confidence: 99%
“…In RA, miRNAs act as proinflammatory or anti-inflammatory regulators at the post-transcriptional level. 44 Up until now, the role of miRNA during melatonin administration in RA has not been described. We performed four miRNA prediction programs (TargetScan, miRmap, miR-Walk, and RNAhybrid) and identified that miR-3150a-3p is a candidate miRNA that binds to both 3′UTRs of IL-1β and TNF-α ( Figure 4A).…”
Section: Il-1β Production Via the Upregulation Of Mir-3150a-3pmentioning
confidence: 99%
“…Dysregulation of micro RNAs (miRNAs) plays an important role in the pathogenesis of RA . Alterations in the expression level of different miRNAs may contribute to the development of autoimmunity, particularly in RA . miRNAs may be implicated in the remodeling of bone and cartilage through regulation of osteoclastogenesis, osteoblastogenesis and differentiation of articular chondrocytes.…”
Section: Introductionmentioning
confidence: 99%